Instruments de manutention des malades, usage du corps et appropriation des gestes collectifs des soignants - Sandrine Caroly; Stéphanie Moisan; Isabelle Juret; Céline Brinon; Marie-Pierre Guillo-Bailly; Yves Roquelaure (Perspectives Interdisciplinaires sur le Travail et la Santé)
The aim of this article is twofold: 1) to understand the consequences of using patient handling tools on the risk factors for Upper Extremity Musculoskeletal Disorders (UEMSDs) and low back pain; and 2) to make recommendations to health professionals about how to improve their relationship with the tools as well as about the utilization criteria and methods on which designers can base their work. The reasons for studying this aspect was the low use of patient handling tools in real practice, the high number of low back injuries during patient handling, and the concerns of UHC management about the purchase of equipment. The chosen methodology was based on an ergonomic diagnosis of patient handling activities, from observations accompanied by measurements comparing three patient handling tools (quilted pads, mobile equipment, rail on the ceiling), data resulting from testing new material, and epidemiological data on the relationships between handling constraints and health impacts.